The iron-sulfur scaffold protein HCF101 unveils the complexity of organellar evolution in SAR, Haptista and Cryptista - Pyrih, Jan; Žárský, Vojtěch; Fellows, Justin D; Grosche, Christopher; Wloga, Dorota; Striepen, Boris; Maier, Uwe G; Tachezy, Jan (BMC ecology and evolution, 2021)
BACKGROUND: Nbp35-like proteins (Nbp35, Cfd1, HCF101, Ind1, and AbpC) are P-loop NTPases that serve as components of iron-sulfur cluster (FeS) assembly machineries. In eukaryotes, Ind1 is present in mitochondria, and its function is associated with the assembly of FeS clusters in subunits of respiratory Complex I, Nbp35 and Cfd1 are the components of the cytosolic FeS assembly (CIA) pathway, and HCF101 is involved in FeS assembly of photosystem I in plastids of plants (chHCF101). The AbpC protein operates in Bacteria and Archaea. To date, the cellular distribution of these proteins is considered to be highly conserved with only a few exceptions. RESULTS: We searched for the genes of all members of the Nbp35-like protein family and analyzed their targeting sequences. Nbp35 and Cfd1 were predicted to reside in the cytoplasm with some exceptions of Nbp35 localization to the mitochondria; Ind1was found in the mitochondria, and HCF101 was predicted to reside in plastids (chHCF101) of all photosynthetically active eukaryotes. Surprisingly, we found a second HCF101 paralog in all members of Cryptista, Haptista, and SAR that was predicted to predominantly target mitochondria (mHCF101), whereas Ind1 appeared to be absent in these organisms. We also identified a few exceptions, as apicomplexans possess mHCF101 predicted to localize in the cytosol and Nbp35 in the mitochondria. Our predictions were experimentally confirmed in selected representatives of Apicomplexa (Toxoplasma gondii), Stramenopila (Phaeodactylum tricornutum, Thalassiosira pseudonana), and Ciliophora (Tetrahymena thermophila) by tagging proteins with a transgenic reporter. Phylogenetic analysis suggested that chHCF101 and mHCF101 evolved from a common ancestral HCF101 independently of the Nbp35/Cfd1 and Ind1 proteins. Interestingly, phylogenetic analysis supports rather a lateral gene transfer of ancestral HCF101 from bacteria than its acquisition being associated with either α-proteobacterial or cyanobacterial endosymbionts. CONCLUSION: Our searches for Nbp35-like proteins across eukaryotic lineages revealed that SAR, Haptista, and Cryptista possess mitochondrial HCF101. Because plastid localization of HCF101 was only known thus far, the discovery of its mitochondrial paralog explains confusion regarding the presence of HCF101 in organisms that possibly lost secondary plastids (e.g., ciliates, Cryptosporidium) or possess reduced nonphotosynthetic plastids (apicomplexans).
Keywords: železo; proteiny obsahující železo a síru; Plastid; Iron; Evolution; Cryptosporidiosis; Iron-Sulfur Proteins; Phylogeny; kryptosporidióza; HCF101; Iron-sulfur cluster; Ind1; Cryptosporidium; zvířata; Mitochondrion; fylogeneze; Sulfur; síra; Animals